Wear-resistant steel plate
By formulating wear-resistant steel with reduced Ni and Mo content, utilizing Cr and controlling microstructural elements, the steel achieves enhanced abrasion resistance and toughness at lower costs.
Patent Information
- Application Number
- JP2020127724
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-28
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2040-07-28
AI Technical Summary
Existing abrasion-resistant steels rely heavily on expensive elements like Ni and Mo, which increase costs while compromising on alloy efficiency in terms of abrasion resistance and low-temperature toughness.
A wear-resistant steel composition with a reduced content of Ni and Mo, utilizing Cr as a primary hardening element, along with controlled carbon content and quenching stop temperature to suppress cementite precipitation and coarsening, resulting in a microstructure predominantly composed of martensite and lower bainite.
The solution achieves excellent abrasion resistance and low-temperature toughness while significantly reducing alloy costs, making it possible to produce inexpensive yet effective abrasion-resistant steels.
Smart Images

Figure 0007667404000001 
Figure 0007667404000002 
Figure 0007667404000003
Abstract
Description
[Technical field]
[0001] The present invention relates to wear-resistant steel. [Background technology]
[0002] Wear-resistant steels are required to have hardness near the surface layer, and therefore contain elements that enhance hardenability. Cr, Ni, and Mo are elements that enhance hardenability. Wear-resistant steels containing Cr, Ni, Mo, etc. have been proposed (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-204575 [Patent Document 2] Japanese Patent Application Publication No. 10-102185 [Patent Document 3] Japanese Patent Application Publication No. 59-129724 [Patent Document 4] Japanese Patent Application Publication No. 59-70721 Summary of the Invention [Problem to be solved by the invention]
[0004] The wear-resistant steels of Patent Documents 1 and 2 contain 1.0 mass % or more of Mo. The wear-resistant steels of Patent Documents 3 and 4 contain 2.0 mass % or more of Ni. Ni and Mo are expensive elements, and it is desirable to reduce their content from the viewpoint of alloy costs. In view of the above circumstances, the object of the present invention is to provide a wear-resistant steel that is excellent in wear resistance and low-temperature toughness while suppressing the use of expensive elements such as Ni and Mo. [Means for solving the problem]
[0005] The gist of the present invention is as follows.
[0006] (1) Chemical composition, in mass percent: C: 0.08% or more, 0.20% or less, Si: 0.01% or more, 0.50% or less, Mn: 0.10% or more, 2.00% or less, P: 0.015% or less, S: 0.0300% or less, Cr: 2.00% or more, 8.00% or less, N: 0.008% or less, Cu: 0% or more, 0.50% or less, Ni: 0% or more, 0.50% or less, Mo: 0% or more, 0.50% or less, V: 0% or more, 0.500% or less, B: 0% or more, 0.0050% or less, Al: 0% or more, 0.300% or less, Ti: 0% or more, 0.100% or less, Nb: 0% or more, 0.100% or less, Ca: 0% or more, 0.0100% or less, Mg: 0% or more, 0.0100% or less, REM: 0% or more, 0.0100% or less, Remainder: Fe and impurities It consists of: In a cross section in the thickness direction, the cementite contained in the metal structure is, in terms of area%, 0% or more and 0.5% or less, and the average circular equivalent diameter of the cementite is 500 nm or less, In a 400 μm × 400 μm region, among crystal grains surrounded by high-angle grain boundaries of 15° or more, the average grain size of the 10 largest crystal grains is 40 μm or less; Surface hardness is 360HV10 or more. Abrasion-resistant steel with a Charpy absorbed energy of 27 J or more at -40°C. (2) The wear-resistant steel according to (1) above, having a hardness of 360 HV10 or more at the center in the thickness direction. Effect of the Invention
[0007] According to the present invention, a wear-resistant steel having excellent wear resistance and low-temperature toughness is provided while suppressing the use of expensive elements such as Ni and Mo. The reduction in alloy cost of the wear-resistant steel makes it possible to provide an inexpensive wear-resistant steel. Therefore, the present invention makes a significant contribution to industry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, a steel plate will be mainly described as an abrasion-resistant steel according to one embodiment of the present invention (hereinafter referred to as "this embodiment"). In the present specification, the upper limit of a numerical range described in stages may be replaced with the upper limit of another numerical range described in stages, and the lower limit of a numerical range described in stages may be replaced with the lower limit of another numerical range described in stages. The upper limit or lower limit may be replaced with a value shown in the examples. The term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. First, the results of the research conducted by the present inventors that led to the completion of the present invention and the new findings obtained will be described in detail.
[0009] Cr is a cheaper element than Ni and Mo. By suppressing the Ni and Mo contents and increasing the Cr content, it is possible to reduce the cost of the wear-resistant steel. As a result of the studies by the present inventors, it was found that the Cr content required for an alloy-saving wear-resistant steel when Ni and Mo are not intentionally contained or when the Ni and Mo contents are each suppressed to 0.50% or less is 2.00% or more. On the other hand, in order to ensure the surface hardness of the wear-resistant steel, it is preferable to increase the C content, but this causes a problem of reduced toughness.
[0010] The present inventors have succeeded in achieving both surface hardness and toughness of wear-resistant steel by suppressing the precipitation and coarsening of cementite. As a result of the study by the present inventors, it was found that the precipitation and coarsening of cementite can be suppressed and toughness can be ensured by limiting the C content and the quenching stop temperature. Specifically, it was found that the precipitation and coarsening of cementite can be effectively suppressed by setting the C content to 0.20% or less and the quenching stop temperature to 200°C or less. It was found that when the area fraction of cementite is 0.5% or less, the average circle equivalent diameter is 500nm or less, and the surface hardness is 360HV10 or more in Vickers hardness, the total area fraction of one or both of martensite and lower bainite is 95% or more.
[0011] <Chemical composition> Next, the alloying elements constituting the chemical composition of the steel plate according to this embodiment will be described. In the following description of the alloying elements, "%" for the content means "mass %".
[0012] [C: 0.08% or more, 0.20% or less] C (carbon) is an element that improves the hardenability of steel and increases its hardness. From the viewpoint of ensuring hardness, the C content is 0.08% or more. The C content is preferably 0.10% or more. On the other hand, C is an element that forms cementite. From the viewpoint of ensuring toughness, the C content is 0.20% or less. The C content is preferably 0.18% or less, and more preferably 0.15% or less.
[0013] [Si: 0.01% or more, 0.50% or less] Si (silicon) is a deoxidizing element. The Si content is 0.01% or more from the viewpoint of obtaining the deoxidizing effect. The Si content is preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, the Si content is 0.50% or less from the viewpoint of ensuring toughness. The Si content is preferably 0.40% or less, and more preferably 0.30% or less.
[0014] [Mn: 0.10% or more, 2.00% or less] Mn (manganese) is an element that enhances the hardenability of steel. From the viewpoint of ensuring hardness, the Mn content is 0.10% or more. The Mn content is preferably 0.50% or more, more preferably 0.80% or more, and further preferably 1.00% or more. On the other hand, Mn is an element that embrittles the grain boundaries of steel. From the viewpoint of ensuring toughness, the Mn content is 2.00% or less. The Mn content is preferably 1.80% or less, and more preferably 1.60% or less.
[0015] [P:0.015% or less] P (phosphorus) is an element that is mixed into steel during the manufacturing process. The P content is 0.015% or less from the viewpoint of ensuring toughness. The P content is preferably 0.012% or less, and more preferably 0.010% or less. It is preferable to reduce the P content, and although there is no lower limit, it may be more than 0% from the viewpoint of manufacturing costs. The P content may be 0.001% or more.
[0016] [S:0.0300% or less] S (sulfur) is an element that is mixed into steel during the manufacturing process. The S content is 0.0300% or less from the viewpoint of ensuring toughness. The S content is preferably 0.0050% or less, and more preferably 0.0030% or less. It is preferable to reduce the S content, and although there is no lower limit, it may be more than 0% from the viewpoint of manufacturing costs. The S content may be 0.0001% or more.
[0017] [Cr:2.00% or more, 8.00% or less] Cr (chromium) is an element that enhances the hardenability of steel. Cr is an important element from the viewpoint of ensuring the hardenability and toughness of the wear-resistant steel by suppressing the content of expensive elements such as Ni and Mo. The Cr content is 2.00% or more from the viewpoint of ensuring the hardenability. The Cr content is preferably 2.10% or more, and more preferably 2.40% or more. On the other hand, the Cr content is 8.00% or less, and may be 7.50% or less from the viewpoint of cost. The Cr content is preferably 5.00% or less, and more preferably 3.00% or less.
[0018] [N:0.0080% or less] N (nitrogen) is an element that is mixed into steel during the manufacturing process. The N content is 0.0080% or less from the viewpoint of ensuring toughness. The N content is preferably 0.0070% or less, and more preferably 0.0060% or less. It is preferable to reduce the N content, and there is no lower limit, but from the viewpoint of manufacturing costs, it may be more than 0%. When Al or Ti is contained, it combines with N to form fine nitrides such as AlN and TiN. The N content is preferably 0.0010% or more, and more preferably 0.0020% or more, from the viewpoint of refining the metal structure by the nitrides.
[0019] In order to improve hardenability without excessively increasing production costs, the wear-resistant steel according to this embodiment may contain one or more of Cu, Ni, Mo, V, and B within the following ranges, as necessary.
[0020] [Cu: 0% or more, 0.50% or less] Cu (copper) is an element that enhances the hardenability of steel. The lower limit of the Cu content is not limited and may be 0%. In order to reliably obtain the effect, the Cu content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, from the viewpoint of cost, the Cu content is 0.50% or less. The Cu content is preferably 0.30% or less, more preferably 0.10% or less, and further preferably 0.05% or less.
[0021] [Ni: 0% or more, 0.50% or less] Ni (nickel) is an element that enhances the hardenability of steel. The lower limit of the Ni content is not limited and may be 0%. In order to obtain the effect, the Ni content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, from the viewpoint of cost, the Ni content is 0.50% or less. The Ni content is preferably 0.30% or less, more preferably 0.10% or less, and further preferably 0.05% or less.
[0022] [Mo: 0% or more, 0.50% or less] Mo (molybdenum) is an element that enhances the hardenability of steel. The lower limit of the Mo content is not limited and may be 0%. In order to obtain the effect, the Mo content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, from the viewpoint of cost, the Mo content is 0.50% or less. It is preferably 0.30% or less, more preferably 0.10% or less, and further preferably 0.05% or less.
[0023] [V: 0% or more, 0.500% or less] V (vanadium) is an element that forms precipitates such as carbides and nitrides, and has the effect of improving hardenability. The lower limit of the V content is not limited and may be 0%. In order to obtain this effect, the V content is preferably 0.003% or more, and more preferably 0.005% or more. On the other hand, from the viewpoint of cost, the V content is 0.500% or less. It is preferably 0.300% or less, more preferably 0.100% or less, and further preferably 0.050% or less.
[0024] [B: 0% or more, 0.0050% or less] B (boron) is an element that significantly improves the hardenability of steel even in a small amount. The lower limit of the B content is not limited and may be 0%. In order to obtain the effect, the B content is preferably 0.0003% or more, more preferably 0.0005% or more, and further preferably 0.0008% or more. On the other hand, even if B is excessively contained, the effect is saturated, so the B content is 0.0050% or less. The B content is preferably 0.0045% or less, and more preferably 0.0040% or less.
[0025] The wear-resistant steel according to this embodiment may contain one or more of Al, Ti, Nb, Ca, Mg and REM, which form compounds such as carbides, nitrides, oxides and sulfides, as necessary.
[0026] [Al: 0% or more, 0.300% or less] Al (aluminum) is a deoxidizing element and also an element that forms nitrides. The lower limit of the Al content is not limited and may be 0%. In order to obtain the effect of deoxidization, the Al content is preferably 0.005% or more. From the viewpoint of refining the metal structure by AlN, the Al content is more preferably 0.010% or more. On the other hand, from the viewpoint of suppressing the generation of coarse inclusions, the Al content is 0.300% or less. The Al content is preferably 0.100% or less, more preferably 0.070% or less.
[0027] [Ti: 0% or more, 0.100% or less] Ti (titanium) is a deoxidizing element and also an element that forms nitrides. In addition, when B is contained in steel, Ti is used to suppress the formation of BN and improve hardenability. The lower limit of the Ti content is not limited and may be 0%. In order to obtain the effect of deoxidization, the Ti content is preferably 0.003% or more. From the viewpoint of refining the metal structure by TiN, the Ti content is more preferably 0.005% or more, and further preferably 0.010% or more. On the other hand, from the viewpoint of suppressing the generation of coarse inclusions, the Ti content is 0.100% or less. The Ti content is more preferably 0.050% or less, and further preferably 0.030% or less.
[0028] [Nb: 0% or more, 0.100% or less] Nb (niobium) is an element that forms precipitates such as carbides and nitrides. The lower limit of the Nb content is not limited and may be 0%. From the viewpoint of refining the metal structure by the precipitates, the Nb content is preferably 0.003% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, even if Nb is excessively contained, the effect is saturated, so the Nb content is 0.100% or less. The Nb content is preferably 0.050% or less, and even more preferably 0.030% or less.
[0029] [Ca: 0% or more, 0.0100% or less] Ca (calcium) is an element that forms oxides and sulfides and controls the morphology of inclusions. The lower limit of the Ca content is not limited and may be 0%. In order to obtain the effect, the Ca content is preferably 0.0003% or more. The Ca content is more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, from the viewpoint of suppressing the formation of coarse inclusions, the Ca content is 0.0100% or less. The Ca content is preferably 0.0080% or less, and more preferably 0.0060% or less.
[0030] [Mg: 0% or more, 0.0100% or less] Mg (magnesium) is an element that forms oxides and sulfides and controls the morphology of inclusions. The lower limit of the Mg content is not limited and may be 0%. In order to obtain the effect, the Mg content is preferably 0.0003% or more, more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, from the viewpoint of cost, the Mg content is 0.0100% or less. The Mg content is preferably 0.0080% or less, and more preferably 0.0060% or less.
[0031] [REM: 0% or more, 0.0100% or less] REM (rare earth elements) refers to a collective term for 17 elements in total, including two elements, Sc and Y, and 15 lanthanoid elements, such as La, Ce, and Nd. The REM content refers to the total content of the above 17 elements. REM is an element that forms oxides and sulfides and controls the morphology of inclusions. The lower limit of the REM content is not limited and may be 0%. In order to obtain the effect, the Mg content is preferably 0.0003% or more, more preferably 0.0005% or more, and further preferably 0.0010% or more. On the other hand, from the viewpoint of cost, the REM content is 0.0100% or less. The REM content is preferably 0.0080% or less, and more preferably 0.0060% or less.
[0032] The balance of the above chemical components of the steel according to this embodiment is Fe and impurities. Here, the impurities are components that are not intentionally contained when the wear-resistant steel according to this embodiment is industrially produced, but are mixed in due to raw materials such as ores and scraps, or various factors in the production process. The inclusion of impurities is permitted within a range that does not adversely affect the properties of the wear-resistant steel according to this embodiment.
[0033] <Metal structure> Next, the metal structure of the wear-resistant steel according to this embodiment will be described. In the following, "%" in the metal structure means "area %". In the wear-resistant steel according to the present embodiment, the cementite contained in the metal structure is 0% or more and 0.5% or less in area percentage. The average circle equivalent diameter of the cementite is 500 nm or less. In a 400 μm×400 μm region, among the crystal grains surrounded by high-angle grain boundaries of 15° or more, the average grain size of the 10 crystal grains in descending order of grain size is 40 μm or less.
[0034] The metal structure of the wear-resistant steel according to this embodiment may have the area ratio and average equivalent circle diameter of cementite and the average grain size within the above-mentioned range. For example, when upper bainite or pearlite is generated, the area ratio of cementite increases and tends to become coarse. When ferrite is generated, the hardness tends to be insufficient and the toughness may be reduced. The retained austenite becomes hard martensite (deformation-induced martensite) due to deformation and may reduce the toughness. Therefore, the metal structure of the wear-resistant steel according to this embodiment is preferably composed of one or both of martensite and lower bainite. The total area ratio of martensite and lower bainite is preferably 95% or more. The remainder excluding martensite and lower bainite is composed of one or more of ferrite, pearlite, retained austenite, and upper bainite.
[0035] Martensite and lower bainite are lath-shaped hard phases, and are generally distinguished by the presence or absence of cementite. When the metal structure of the wear-resistant steel according to this embodiment is composed of martensite and lower bainite, the metal structure containing cementite is regarded as lower bainite. In this embodiment, it is not necessary to distinguish between martensite and lower bainite. When ferrite, pearlite, retained austenite, and upper bainite are not observed with an optical microscope, it is determined that the metal structure is composed of one or both of martensite and lower bainite. The wear-resistant steel according to this embodiment may contain a metal structure other than martensite and lower bainite, so long as the area ratio and average equivalent circle diameter of cementite and the average grain size of the crystals are within the above-mentioned ranges.
[0036] When the thickness of the wear-resistant steel is less than 16 mm, the metal structure is observed at a portion from the surface to the thickness direction at 1 / 2 of the thickness (hereinafter also referred to as the "1 / 2t portion"). When the thickness of the wear-resistant steel is 16 mm or more, the metal structure is observed at a portion from the surface to the thickness direction at 1 / 4 of the thickness (hereinafter also referred to as the "1 / 4t portion"). The observation surface of the sample used for observing the metal structure is a cross section cut in the thickness direction along the L (longitudinal) direction (rolling direction) of the sample (hereinafter sometimes referred to as the "L (longitudinal) direction cross section of the sample"), which is wet polished and etched with nital. The metal structure is observed at a magnification of 400 times, and the presence or absence of ferrite, pearlite, retained austenite, and upper bainite is determined by observing five fields of view.
[0037] [Area ratio of cementite: 0% or more, 0.5% or less] When the metal structure of the wear-resistant steel according to the present embodiment is made of martensite, the area ratio of cementite is 0%. When the metal structure of the wear-resistant steel according to the present embodiment is made of martensite and lower bainite, the metal structure containing cementite is regarded as lower bainite. From the viewpoint of ensuring toughness, the area ratio of cementite is 0.5% or less. The area ratio of cementite is preferably 0.4% or less, and more preferably 0.3% or less. When the quenching stop temperature is lowered, the generation of upper bainite and pearlite is suppressed, and the area ratio of cementite is reduced.
[0038] The cementite area ratio is measured by a scanning electron microscope (hereinafter referred to as "SEM"). When the thickness of the wear-resistant steel is less than 16 mm, the cementite area ratio is measured at the 1 / 2t section. When the thickness of the wear-resistant steel is 16 mm or more, the cementite area ratio is measured at the 1 / 4t section. The observation surface of the sample used to measure the cementite area ratio is the L (longitudinal) cross section of the sample, which is electrolytically etched. The cementite area ratio is measured by image analysis of a photograph taken at 30,000 times magnification.
[0039] [Average equivalent circular diameter of cementite: 500 nm or less] The average equivalent circle diameter of cementite is 500 nm or less from the viewpoint of ensuring toughness. The average equivalent circle diameter of cementite is preferably 300 nm or less. The average equivalent circle diameter of cementite may be 50 nm or more, or may be 100 nm or more. The average equivalent circle diameter of cementite is calculated from the area (total) of cementite obtained by image analysis of the SEM photograph used to measure the area ratio, and the number of cementite. That is, the average equivalent circle diameter is calculated from the average area of cementite obtained by dividing the total area of cementite by the number of cementite. When the area ratio of cementite is 0%, the average equivalent circle diameter is 0 nm. When the quenching stop temperature is lowered, the generation of upper bainite and pearlite is suppressed, and the average equivalent circle diameter of cementite becomes smaller. The cementite contained in upper bainite and pearlite has a large average equivalent circle diameter and area ratio. If the area fraction of cementite is 0.5% or less and the average equivalent circle diameter is 500 nm or less, it may be determined that the total area fraction of upper bainite and pearlite is less than 5%.
[0040] [Top 10 grain sizes surrounded by high-angle boundaries of 15° or more: 40μm or less] In a 400 μm x 400 μm region, the average of the top 10 grain sizes (the 10 largest grain sizes) surrounded by high-angle grain boundaries with a crystal orientation difference of 15° or more is 40 μm or less. Hereinafter, grain sizes surrounded by high-angle grain boundaries with a crystal orientation difference of 15° or more are referred to as high-angle grain sizes. As the high-angle grain size increases, fracture becomes more likely to occur, and as the high-angle grain size decreases, toughness improves. The high-angle grain size is evaluated as the average value of the top 10 grains (the 10 largest grains) within a 400 μm x 400 μm region. The high-angle grain size is more preferably 30 μm or less.
[0041] In this embodiment, the high-angle grain size is measured by electron backscattered diffraction pattern (hereinafter also referred to as "EBSD"). The EBSD measurement is performed in a field of view of 400 μm × 400 μm at a pitch of 0.4 μm. The grain size distribution is displayed by a commercially available analysis software (OIM-Analysis manufactured by TSL Co., Ltd.), and the average grain size of the top 10 crystal grains surrounded by high-angle grain boundaries of 15° or more is calculated. The EBSD measurement is performed at the 1 / 2t part when the thickness of the wear-resistant steel is less than 16 mm. When the thickness is 16 mm or more, the EBSD measurement is performed at the 1 / 4t part. The sample used for the EBSD measurement has an observation surface of 10 mm square, and is cut out from the position (1 / 4 width) of 1 / 4 of the sheet width from the end of the width direction of the steel sheet. The observation surface is a cross section in the L (longitudinal) direction of the sample, and is electrolytically polished.
[0042] Next, the surface hardness, the hardness at the 1 / 2t portion, and the low-temperature toughness of the wear-resistant steel according to this embodiment will be described.
[0043] [Surface hardness: 360HV10 or higher] The surface hardness of the wear-resistant steel according to this embodiment is 360HV10 or more in Vickers hardness in order to ensure wear resistance. The surface hardness of the wear-resistant steel is preferably 400HV10 or more, and the higher the better, with no upper limit. The surface hardness of the wear-resistant steel may be 450HV10 or less from the viewpoint of ensuring toughness. The surface hardness of wear-resistant steel is measured at a position 0.7 mm from the surface of the wear-resistant steel in the thickness direction, taking into account the effects of decarburization. The Vickers hardness test is performed in accordance with JIS Z 2244:2009, and the load is 10 kgf. The Vickers hardness is the average value of three points measured on the L (longitudinal) cross section of the sample. If the surface hardness is 360 HV10 or more in Vickers hardness, the total area ratio of ferrite and retained austenite may be determined to be less than 5%.
[0044] [Hardness at the center of the thickness direction: 360HV10 or more] The center of the thickness direction of the wear-resistant steel is synonymous with the 1 / 2t portion, and hereinafter, the hardness at the center of the thickness direction of the wear-resistant steel is referred to as the 1 / 2t portion hardness. From the viewpoint of preventing deterioration of wear resistance due to use, the 1 / 2t portion hardness is preferably 360HV10 or more in Vickers hardness, more preferably 380HV10 or more. The 1 / 2t portion hardness is further preferably 400HV10 or more, and the higher the better, and there is no upper limit. From the viewpoint of ensuring toughness, the 1 / 2t portion hardness may be 450HV10 or less. The Vickers hardness test is performed in accordance with JIS Z 2244:2009, and the load is 10kgf. The Vickers hardness is the average value of three points measured on the L (longitudinal) cross section of the sample. The 1 / 2t portion hardness is ensured by increasing the content of an alloy that enhances hardenability and increasing the cooling rate of quenching.
[0045] [Average Charpy absorbed energy at -40℃: 27J or more] Abrasion-resistant steels are sometimes used in cold regions or at high altitudes. In order to suppress breakage due to impact during processing and use, it is necessary for the abrasion-resistant steel to ensure toughness at -40°C. From this perspective, the abrasion-resistant steel according to this embodiment has an average Charpy absorbed energy of 27 J or more at -40°C. The average Charpy absorbed energy at -40°C is preferably 50 J or more. The higher the average Charpy absorbed energy at -40°C, the more preferable it is, and although there is no upper limit, it may be 100 J or less.
[0046] Charpy tests are performed using full-size test pieces with V notches in accordance with JIS Z 2242:2018. When the thickness of the wear-resistant steel is 12 mm or less, a sub-size test piece of 5 mm is used. The location of the Charpy test piece is the 1 / 4t section for wear-resistant steel with a plate thickness of 16 mm or more, and the 1 / 2t section for wear-resistant steel with a plate thickness of less than 16 mm. The longitudinal direction of the Charpy test piece is the rolling direction. Considering the variation in the measurement values, the average Charpy absorbed energy is the arithmetic average of the measurements of three test pieces.
[0047] The shape of the wear-resistant steel according to this embodiment is not particularly limited, and may be a steel plate, a steel strip, a shaped steel, a steel pipe, a steel bar, a steel wire, or the like. The thickness of the steel material such as the steel plate, the steel strip, the shaped steel, the steel pipe, or the like is not particularly limited, and may be, for example, 8 mm or more and 50 mm or less. The thickness of the steel material may be 10 mm or more, or may be 16 mm or more. The thickness of the steel material may be 45 mm or less, or may be 40 mm or less. When the wear-resistant steel according to this embodiment is a steel bar, the diameter may be regarded as the thickness and a Vickers hardness measurement and a Charpy test may be carried out.
[0048] <Manufacturing method> Next, a method for producing the wear-resistant steel according to this embodiment will be described.
[0049] The wear-resistant steel according to this embodiment is manufactured by melting steel, adjusting the components, and casting the resulting steel billet as a steel material. The steel material is hot-rolled and either quenched as is or air-cooled. After air-cooling, the steel is reheated and quenched. After quenching is performed after hot rolling, reheating and quenching may also be performed.
[0050] The manufacturing method of the steel material used to manufacture the wear-resistant steel according to this embodiment is not limited, and the steel material may be manufactured by a known method. For example, steel slabs are produced by melting in a normal refining process using a converter, an electric furnace, or the like, and then by a known method such as a continuous casting method or an ingot casting-blooming method. The steel billet is preferably cooled after casting and c3 The steel slab is reheated to a temperature equal to or higher than the transformation point and hot rolled. If the steel slab after continuous casting is not cooled to 400°C or lower and is charged into a heating furnace by hot charging, the coarse austenite formed during casting may remain in the steel slab after heating. In order to promote the refinement of the structure of the wear-resistant steel, it is preferable that the steel slab after continuous casting is once cooled to 400°C or lower.
[0051] In hot rolling, the surface temperature of the rolled material is A r3 It is performed in a temperature range above the transformation point. r3The transformation point is the temperature at which transformation from austenite to ferrite begins during cooling. The heating temperature of the steel material before hot rolling is preferably 900°C or higher, more preferably 1000°C or higher, and even more preferably 1100°C or higher. The heating temperature is preferably 1330°C or lower in order to suppress coarsening of crystal grains. The heating temperature is more preferably 1200°C or lower, and even more preferably 1150°C or lower.
[0052] In hot rolling of wear-resistant steel, it is preferable to promote recrystallization to reduce the grain size of austenite from the viewpoint of ensuring low-temperature toughness. In order to promote recrystallization, the rolling reduction in the temperature range of 1000°C or higher is preferably 50% or more. The rolling reduction in the temperature range of 1000°C or higher (simply referred to as the rolling reduction) is calculated from the thickness of the steel material before hot rolling and the thickness of the material to be rolled at 1000°C by the following formula: Reduction rate (%) = 100 × {(thickness of steel material) - (thickness of material being rolled at 1000℃)} / thickness of steel material
[0053] The end temperature of hot rolling is set to A in order to prevent the formation of ferrite. r3 The temperature is equal to or higher than the transformation point. When the rolled material is quenched as is after completion of hot rolling, the end temperature of hot rolling is 770°C or higher. On the other hand, from the viewpoint of refining the metal structure, the end temperature of hot rolling is preferably 900°C or lower, more preferably 850°C or lower. The thickness of the rolled material after completion of hot rolling is the thickness of the wear-resistant steel, and is, for example, 8 mm or more and 50 mm or less.
[0054] The rolled material after hot rolling is either directly quenched or air-cooled. The air-cooled rolled material is reheated and quenched. The process in which the rolled material after hot rolling is directly quenched is called direct quenching. The process in which the rolled material after hot rolling is air-cooled, reheated, and quenched is called reheating quenching. The rolled material that has been quenched after hot rolling may be reheated and quenched. The reheating temperature is set to A from the viewpoint of preventing the formation of ferrite. c3Any temperature may be used as long as it is equal to or higher than the transformation point. The reheating temperature is preferably 850°C or higher, and more preferably 900°C or higher. From the viewpoint of refining the metal structure, the reheating temperature is preferably 1150°C or lower. The reheating temperature is more preferably 1050°C or lower, and further preferably 1000°C or lower.
[0055] The following explanation of the starting temperature, cooling rate, and stopping temperature of quenching does not differ between direct quenching and reheating quenching. The starting temperature of quenching is 770°C or higher from the viewpoint of preventing the formation of ferrite. The cooling rate of quenching is 3°C / sec or higher at the surface temperature of the rolled material from the viewpoint of preventing the formation of ferrite and suppressing the precipitation and growth of cementite. The faster the cooling rate, the better, but there is a limit depending on the capacity of the cooling equipment, the thickness of the rolled material, etc., and it may be 50°C / sec or less.
[0056] The quenching stop temperature is 200°C or less at the surface of the rolled material from the viewpoint of preventing the formation of ferrite and suppressing the precipitation and growth of cementite. The quenching stop temperature is preferably 100°C or less at the surface of the rolled material from the viewpoint of suppressing the growth of cementite in particular.
[0057] Here, A c3 is the transformation start temperature when heated, calculated as follows, A r3 is the transformation start temperature upon cooling, calculated as follows, using the chemical composition of the steel.
[0058] A c3 (℃) = 902-255 x C + 19 x Si-11 x Mn-5 x Cr + 13 x Mo-20 x Ni + 55 x V A r3 (℃) = 868-396 x C + 24.6 x Si-68.1 x Mn-24.8 x Cr In the above formula, C, Si, Mn, Cr, Mo, Ni, and V mean the contents expressed in mass%. EXAMPLES
[0059] Examples of the present invention are described below. However, the examples shown below are merely examples of the present invention, and the present invention is not limited to the examples described below. Example 1 is an example of direct quenching, and Example 2 is an example of reheat quenching.
[0060] <Example 1> The thickness of the steel slab produced by melting steel in a converter and continuous casting was 245 mm. Samples were taken from the steel slab, and the chemical components were analyzed using X-ray fluorescence analysis, combustion-infrared absorption analysis, inert gas fusion analysis, inductively coupled plasma mass spectrometry (ICP mass spectrometry), etc. The results are shown in Table 1. In Tables 1 to 3, underlines indicate values or conditions outside the range of the present invention.
[0061] [Table 1]
[0062] The billet was hot-rolled, and the rolled material was quenched to produce steel plate (wear-resistant steel). The heating temperature for hot rolling was A c3 The transformation point is above the end temperature. r3 In the hot rolling process, the material was rolled at a rolling reduction rate of 50% or more in a temperature range of 1000°C or higher. The steel numbers of the steel pieces used in the hot rolling, the start temperature of quenching, the cooling rate, the stop temperature and the thickness of the steel plates are shown in Table 2.
[0063] (Metal structure observation) Observation of the metal structure of each obtained thick steel plate was performed at the 1 / 2t section when the thickness of the wear-resistant steel was less than 16 mm, and at the 1 / 4t section when the thickness of the wear-resistant steel was 16 mm or more. The observation surface was a cross section in the L (longitudinal) direction of the sample, which was wet polished and etched with nital. Observation of the metal structure was performed at a magnification of 400 times, and the presence or absence of ferrite, pearlite, upper bainite, and retained austenite was determined by observing five fields of view. If a structure other than lower bainite and martensite was observed, it is indicated in Table 2 by the following symbols, and if the following structures were not observed, "-" is recorded. α: Ferrite P: Perlite uB: Upper bainite γ: Retained austenite
[0064] (Measurement of cementite area ratio and average circle equivalent diameter) The samples used for observing the metal structure were electrolytically polished, and the cementite area ratio and equivalent circle diameter were measured using a SEM. The cementite area and number of cementite particles were measured using image analysis of a photograph taken at 30,000x magnification, and the cementite area ratio and average equivalent circle diameter were calculated. The cementite area ratio and average equivalent circle diameter are shown in Table 2.
[0065] (Measurement of effective grain size) In addition, the average of the top 10 grain sizes surrounded by high-angle boundaries of 15° or more was measured by EBSD. EBSD measurements were performed with a field of view of 400 μm × 400 μm and a pitch of 0.4 μm. The average of the top 10 grain sizes surrounded by high-angle boundaries of 15° or more was determined by OIM-Analysis (TSL). The average of the top 10 grain sizes surrounded by high-angle boundaries of 15° or more is shown in Table 2 as the effective grain size.
[0066] (Vickers hardness test) In the L (longitudinal) cross section of the sample, the Vickers hardness of the wear-resistant steel was measured at a position 0.7 mm in the thickness direction from the surface of the wear-resistant steel and at the 1 / 2t part. The Vickers hardness test was performed in accordance with JIS Z 2244:2009, with a load of 10 kgf. The Vickers hardness is the average value of three arbitrary measured points. If the surface hardness is 360HV10 or more, the wear resistance is good, and if the hardness at the 1 / 2t part is 360HV10 or more, the deterioration suppression of wear resistance is also good.
[0067] (Charpy test) Charpy tests were performed using full-size test specimens with V-notches in accordance with JIS Z 2242:2018. The average Charpy absorbed energy was the arithmetic mean of the measurements for three test specimens. The longitudinal direction of the Charpy test specimen was the rolling direction of the steel plate. When the thickness of the wear-resistant steel was 12 mm or less, a 5 mm sub-size test piece was used. The Charpy test pieces were taken from the 1 / 4t section for wear-resistant steel with a plate thickness of 16 mm or more, and from the 1 / 2t section for wear-resistant steel with a plate thickness of less than 16 mm. The Vickers hardness (surface hardness and 1 / 2t hardness) and Charpy absorbed energy (KV2) are shown in Table 2. If the Charpy absorbed energy is 27 J or more, the low-temperature toughness is good.
[0068] [Table 2]
[0069] <Example 2> The billets of steel with the composition shown in Table 1 were hot-rolled, air-cooled, and then reheated and quenched to produce steel plates. The heating temperature for hot rolling was A c3 The transformation point is above the end temperature. r3 The transformation point is above. In the hot rolling process, the rolled material is rolled at a rolling reduction rate of 50% or more in a temperature range of 1000°C or higher. The heating temperature for reheating and quenching is A c3 It is above the transformation point. The steel numbers of the steel pieces used in the hot rolling, the start temperature of quenching, the cooling rate, the stop temperature and the thickness of the steel plates are shown in Table 3.
[0070] The metal structure of each of the obtained steel plates was observed, and the area ratio and average equivalent circle diameter of cementite were measured, and the effective grain size, Vickers hardness, and Charpy absorbed energy were measured in the same manner as in Example 1. The results are shown in Table 3.
[0071] [Table 3]
[0072] As shown in Tables 2 and 3, steel plates satisfying the requirements of the present invention do not contain Ni or Mo, or the Ni and Mo contents are each suppressed to 0.50% or less, and are excellent in wear resistance and low-temperature toughness.
Claims
1. Chemical composition, by mass%, C: 0.08% or more, 0.20% or less, Si: 0.01% or more, 0.50% or less, Mn: 0.10% or more, 2.00% or less, P: 0.015% or less, S: 0.0300% or less, Cr: 2.00% or more, 8.00% or less, N: 0.0080% or less, Cu: 0% or more, 0.50% or less, Ni: 0% or more, 0.50% or less, Mo: 0% or more, 0.50% or less, V: 0% or more, 0.500% or less, B: 0% or more, 0.0050% or less, Al: 0% or more, 0.300% or less, Ti: 0% or more, 0.100% or less, Nb: 0% or more, 0.100% or less, Ca: 0% or more, 0.0100% or less, Mg: 0% or more, 0.0100% or less, REM: 0% or more, 0.0100% or less, Remainder: Fe and impurities It consists of: In a cross section in the thickness direction, the cementite contained in the metal structure is, in terms of area%, 0% or more and 0.5% or less, and the average equivalent circle diameter of the cementite is 500 nm or less, In a 400 μm×400 μm region, among crystal grains surrounded by high-angle grain boundaries of 15° or more, the average grain size of the 10 crystal grains in descending order of grain size is 40 μm or less; The surface hardness is 360HV10 or more, The Charpy absorbed energy at -40°C is 27 J or more, A wear-resistant steel plate having a thickness of 8 mm or more and 50 mm or less.
2. The wear-resistant steel plate according to claim 1, wherein the hardness at the central portion in the thickness direction is 360 HV10 or more.
3. The wear-resistant steel plate according to claim 1 or 2, wherein the S content is 0.0050% or less.
Citation Information
Patent Citations
Manufacture of thick tough steel
JP1984070721A
Production of thick walled ultra high tension steel
JP1984129724A
Production of member with high toughness and high temperature wear resistance and thick steel plate therefor
JP1998102185A
Production of wear resistant member with high toughness and thick steel plate
JP1998204575A
Abrasion resistant steel plate having low-temperature toughness, and manufacturing method thereof
JP2014194042A